As grandes potências e a sua corrida geo-estratégica por Africa - Almeida, E. C. (Figuras &Negócios, 2024)
Abstract: The geo-strategic race of the major world powers for Africa is a complex and multifaceted phenomenon that has intensified in recent decades, especially since the beginning of the 21st century. This growing interest from powers such as the United States of America (USA), China, Russia, India, and the European Union (EU) is driven by various factors, including the abundance of natural resources, the potential for economic growth, the presence of a predominantly young population that is more receptive to new technologies, the geopolitical importance of the region, and the pursuit of strategic alliances.